Effects of Resisted Sprint Training and Traditional Power Training on Sprint, Jump, and Balance Performance in Healthy Young Adults: A Randomized Controlled Trial - Prieske, Olaf; Krüger, Tom; Aehle, Markus; Bauer, Erik; Granacher, Urs (Frontiers in Physiology, 2018)
Power training programs have proved to be effective in improving components of physical fitness such as speed. According to the concept of training specificity, it was postulated that exercises must attempt to closely mimic the demands of the respective activity. When trans-ferring this idea to speed development, the purpose of the present study was to examine the effects of resisted sprint (RST) versus traditional power training (TPT) on physical fitness in healthy young adults. Thirty-five healthy, physically active adults were randomly assigned to a RST (n=10, 23±3 yrs), a TPT (n=9, 23±3 yrs), or a passive control group (n=16, 23±2 yrs). RST and TPT exercised for six weeks with three training sessions/week each lasting 45-60 min. RST comprised frontal and lateral sprint exercises using an expander system with increasing levels of resistance that was attached to a treadmill (h/p/cosmos). TPT included ballistic strength training at 40% of the one-repetition-maximum for the lower limbs (e.g., leg press, knee extensions). Before and after training, sprint (20-m sprint), change-of-direction speed (T-agility test), jump (drop, countermovement jump), and balance performances (Y balance test) were assessed. ANCOVA statistics revealed large main effects of group for 20-m sprint velocity and ground contact time (0.81≤d≤1.00). Post-hoc tests showed higher sprint velocity following RST and TPT (0.69≤d≤0.82) when compared to the control group, but no difference between RST and TPT. Pre-to-post changes amounted to 4.5% for RST (90%CI: [-1.1%;10.1%], d=1.23) and 2.6% for TPT (90%CI: [0.4%;4.8%], d=1.59). Additionally, ground contact times during sprinting were shorter following RST and TPT (0.68≤d≤1.09) compared to the control group, but no difference between RST and TPT. Pre-to-post changes amounted to -6.3% for RST (90%CI: [-11.4%;-1.1%], d=1.45) and -2.7% for TPT (90%CI: [-4.2%;-1.2%], d=2.36). Finally, effects for change-of-direction speed, jump, and balance performance varied from small-to-large. The present findings indicate that 6 weeks of RST and TPT produced similar effects on 20-m sprint performance compared with a passive control in healthy and physically active, young adults. However, no training-related effects were found for change-of-direction speed, jump and balance performance. We conclude that both training regimes can be applied for speed development.